Asymmetrically structured anf-based electromagnetic shielding composite and method of making

CN122970880APending Publication Date: 2026-10-23XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611331387.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]现有电磁屏蔽材料大多为单一结构的均质材料,难以同时实现优异的电磁波吸收性能和低反射特性

Benefits of technology

(1)本发明通过先抽滤成膜-再浇注冷冻的工艺,使反射层与吸收层在湿态条件下利用界面水分诱导去质子化ANF发生局部再质子化和氢键网络重构,实现双层界面的原位结合。再经醋酸促进ANF链间氢键网络进一步恢复与重构,实现稳定的界面结合,消除层间剥离风险;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122970880A_ABST
    Figure CN122970880A_ABST
Patent Text Reader

Abstract

The application discloses an asymmetric ANF-based electromagnetic shielding composite material and a preparation method thereof. The material is a double-layer integrated structure, comprising a reflection layer and an absorption layer. The reflection layer is a ternary dense film composed of ANF, GN and CNT. The absorption layer is a porous aerogel layer composed of ANF and GN. The reflection layer and the absorption layer are integrally combined through the hydrogen bond network and the cross-linking bond of the ANF nanofiber. By constructing the asymmetric absorption layer-reflection layer structure, the electromagnetic wave first enters the absorption layer and is efficiently absorbed and attenuated by the three-dimensional porous ANF / GN aerogel with high specific surface area and dielectric loss capacity. A small amount of penetrating electromagnetic wave is reflected back to the absorption layer after reaching the high-conductivity ANF / GN / CNT reflection layer, and is subjected to secondary absorption. The absorption-reflection-reabsorption mechanism realizes efficient shielding of the electromagnetic wave and significantly reduces the secondary reflection pollution of the electromagnetic wave.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electromagnetic shielding material preparation technology, specifically relating to ANF-based electromagnetic shielding composite materials with asymmetric structures, and also to a method for preparing ANF-based electromagnetic shielding composite materials with asymmetric structures. Background Technology

[0002] Traditional metal-based shielding materials rely primarily on reflection mechanisms, which can easily cause multiple reflections of electromagnetic waves in space, creating new sources of interference. Furthermore, the inherent defects of metal materials, such as high density, susceptibility to corrosion, and complex processing, severely limit their application in aerospace and portable electronic devices. In recent years, carbon-based nanomaterials (such as graphene and carbon nanotubes) and their composite aerogels have been considered among the most promising electromagnetic shielding candidates due to their ultra-low density, high specific surface area, and tunable conductivity. Among these, aramid nanofibers (ANFs), with their excellent mechanical strength, good thermal stability, and abundant polar functional groups, can serve as an ideal polymer matrix for composite with carbon nanofillers, constructing a three-dimensional porous framework that combines mechanical flexibility and functionality.

[0003] Most existing electromagnetic shielding materials are homogeneous materials with a single structure, making it difficult to simultaneously achieve excellent electromagnetic wave absorption performance and low reflection characteristics. While single-reflective shielding materials offer high shielding effectiveness, they can cause severe secondary electromagnetic pollution; single-absorbent materials often have insufficient shielding effectiveness. Therefore, there is an urgent need to develop a novel electromagnetic shielding material that combines high absorption performance with low reflection characteristics. Asymmetric structures typically consist of an absorbing layer with excellent impedance matching and a highly conductive reflective layer, forming a unique absorption-reflection-reabsorption electromagnetic wave attenuation path. Combining thin films with foams or aerogels allows for the retention of the low-density properties of foams or aerogels while enjoying the thinness advantage of thin films. This dual advantage makes these composite materials ideal for absorption-based electromagnetic shielding of next-generation advanced electronic components. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing an asymmetric ANF-based electromagnetic shielding composite material, which achieves efficient electromagnetic wave shielding through an absorption-reflection-reabsorption mechanism.

[0005] Another object of the present invention is to provide an ANF-based electromagnetic shielding composite material with an asymmetric structure.

[0006] The technical solution adopted in this invention is an asymmetric ANF-based electromagnetic shielding composite material, including a reflective layer and an absorber layer; the reflective layer is a ternary dense film composed of ANF, GN and CNT, with a thickness of 10~200μm; the absorber layer is a porous aerogel layer composed of ANF and GN, with a thickness of 0.1~5 mm, and the reflective layer and the absorber layer are integrated through the hydrogen bond network and cross-linking bonds of ANF nanofibers.

[0007] Another technical solution adopted in this invention is a method for preparing ANF-based electromagnetic shielding composite materials with asymmetric structures, specifically as follows: Step 1, Preparation of ANF / DMSO nanofiber dispersion and ANF nanofiber aqueous dispersion; Step 2, preparation of GN / DMSO dispersion and GN aqueous dispersion; Step 3, Preparation of CNT aqueous dispersion; Step 4: Prepare an ANF / GN mixture by ultrasonically mixing the ANF / DMSO nanofiber dispersion and the GN / DMSO dispersion; Step 5: Prepare an ANF\GN\CNT mixture by ultrasonically mixing the ANF nanofiber aqueous dispersion, GN aqueous dispersion and CNT aqueous dispersion; Step 6: Prepare a bilayer ice gel film using a mixture of ANF\GN\CNT and a mixture of ANF / GN; Step 7: Immerse the double-layer ice gel film in an ethanol solution containing acetic acid for solvent replacement treatment, and freeze-dry to obtain an asymmetric ANF-based electromagnetic shielding composite material.

[0008] The invention is further characterized in that, Step 1 specifically involves: Kevlar fibers were placed in a mixed alkaline solvent system consisting of potassium hydroxide and dimethyl sulfoxide and stirred for 5-7 days to form an ANF / DMSO nanofiber dispersion with a concentration of 10-20 mg / mL. Subsequently, deionized water was added to the ANF / DMSO nanofiber dispersion for solvent replacement. The solids were separated by vacuum filtration, and the filter cake was washed repeatedly with deionized water 3-5 times. The resulting ANF nanofiber filter cake was redispersed in deionized water and subjected to shear homogenization at a speed of 8000-15000 rpm for 5-20 min to obtain an ANF nanofiber aqueous dispersion with a concentration of 2-10 mg / mL.

[0009] Step 2 specifically involves: Graphene powder was mixed with polyvinylpyrrolidone and added to deionized water or DMSO. The mixture was then subjected to ultrasonic treatment using an ultrasonic cell disruptor under ice-water bath conditions. The ultrasonic power was 300-700 W and the ultrasonic time was 1-3 h to obtain a GN aqueous dispersion or GN / DMSO dispersion with a concentration of 0.5-5 mg / mL.

[0010] Step 3 specifically involves: Carbon nanotubes were mixed with sodium dodecylbenzenesulfonate and added to deionized water. The mixture was then subjected to ultrasonic treatment using an ultrasonic cell disruptor under ice-water bath conditions. The ultrasonic power was 300-700 W and the ultrasonic time was 1-3 h to obtain an aqueous dispersion of CNT with a concentration of 0.5-5 mg / mL.

[0011] In step 6, specifically: Under vacuum-assisted conditions, the ANF / GN / CNT mixture is filtered to form a dense ANF / GN / CNT film on the filter membrane surface as a reflective layer. After filtration, the mixture is transferred to a polytetrafluoroethylene mold, and the ANF / GN mixture is slowly poured into the mold to cover the ANF / GN / CNT film. Subsequently, the mold with the above-mentioned double-layer structure is pre-frozen for 4-24 hours to form an asymmetric double-layer ice gel film.

[0012] Step 7 specifically involves: A double-layer ice gel film was immersed in an ethanol solution containing acetic acid and subjected to solvent replacement treatment at -10 to -20°C for 36-48 hours. After solvent replacement, it was freeze-dried at -50 to -60°C and 0-10 Pa for 48-72 hours to obtain an asymmetric ANF-based electromagnetic shielding composite material.

[0013] The asymmetric structure of the ANF-based electromagnetic shielding composite material of the present invention can be applied in flexible electronics.

[0014] The beneficial effects of this invention are: (1) This invention utilizes a process of first filtration to form a film and then casting and freezing to enable the reflective layer and absorber layer to undergo local reprotonation and hydrogen bond network reconstruction induced by interfacial moisture under humid conditions, thereby achieving in-situ bonding of the bilayer interface. Acetic acid is then used to further promote the recovery and reconstruction of the hydrogen bond network between ANF chains, achieving stable interfacial bonding and eliminating the risk of interlayer delamination; (2) By constructing an asymmetric absorption layer-reflection layer structure, electromagnetic waves first enter the absorption layer and are efficiently absorbed and attenuated by the three-dimensional porous ANF / GN aerogel with high specific surface area and dielectric loss capability. A small amount of electromagnetic waves that penetrate reach the highly conductive ANF / GN / CNT reflection layer and are reflected back to the absorption layer for secondary absorption. This absorption-reflection-reabsorption mechanism achieves efficient shielding of electromagnetic waves and significantly reduces secondary reflection pollution of electromagnetic waves.

[0015] (3) By independently controlling the composition, thickness and microstructure of the absorption layer (porous aerogel) and the reflective layer (dense film), the electromagnetic parameters and shielding effectiveness of the material can be easily adjusted to achieve efficient shielding for electromagnetic waves of different frequency bands.

[0016] (4) Both the absorption layer and the reflection layer use ANF as the matrix, and ANF is used to form a strong hydrogen bond network and physical entanglement between the two layers, which greatly improves the interfacial bonding strength, avoids the delamination problem of multilayer materials during use, and improves the overall structural stability and mechanical properties of the material.

[0017] (6) Aramid nanofibers endow the material with excellent mechanical properties and heat resistance, making the electromagnetic shielding material lightweight, high-strength and high-temperature resistant, and applicable to aerospace, military equipment, flexible electronics and other fields. Attached Figure Description

[0018] Figure 1 These are photographs of the ANF-based electromagnetic shielding composite material prepared in Example 1. Figure 2a Here is a cross-sectional SEM image of the ANF-based electromagnetic shielding composite material prepared in Example 1; Figure 2b This is a SEM image of the ANF / GN aerogel absorbing layer in the ANF-based electromagnetic shielding composite material prepared in Example 1; Figure 2c This is a SEM image of the ANF crosslinking interface layer in the ANF-based electromagnetic shielding composite material prepared in Example 1; Figure 2d This is a SEM image of the ANF / GN / CNT dense reflective layer in the ANF-based electromagnetic shielding composite material prepared in Example 1; Figure 3 This is a surface SEM image of the absorbing layer in the ANF-based electromagnetic shielding composite material prepared in Example 1; Figure 4 This is a surface SEM image of the reflective layer in the ANF-based electromagnetic shielding composite material prepared in Example 1; Figure 5 This is a diagram showing the overall electromagnetic shielding effectiveness of the ANF-based electromagnetic shielding composite material prepared in Example 1; Figure 6 This is a diagram showing the total electromagnetic shielding effectiveness of the ANF-based electromagnetic shielding composite material prepared in Example 2; Figure 7 This is a diagram showing the total electromagnetic shielding effectiveness of the ANF-based electromagnetic shielding composite material prepared in Example 3; Figure 8 This is a diagram showing the overall electromagnetic shielding effectiveness of the composite material prepared in Comparative Example 1; Figure 9 This is a diagram showing the overall electromagnetic shielding effectiveness of the composite material prepared in Comparative Example 2; Figure 10 This is a comparison chart of the absorption shielding effectiveness, reflection shielding effectiveness, and total shielding effectiveness of the composite materials in the examples and comparative examples. Detailed Implementation

[0019] The present invention will now be described in detail with reference to specific embodiments and accompanying drawings.

[0020] The present invention relates to an asymmetric ANF-based electromagnetic shielding composite material, which is an integrated double-layer structure comprising a reflective layer and an absorber layer. The reflective layer is a ternary dense film composed of ANF, GN, and CNT, with a thickness of 10-200 μm. The absorber layer is a porous aerogel layer composed of ANF and GN, with a thickness of 0.1-5 mm and an anisotropic or isotropic porous structure. The reflective layer and the absorber layer are integrated and bonded together through the hydrogen bond network of ANF nanofibers and amidation crosslinking bonds, with no visible interface.

[0021] The preparation method of the asymmetric ANF-based electromagnetic shielding composite material of the present invention is carried out according to the following steps: Step 1, Preparation of ANF / DMSO nanofiber dispersion and ANF nanofiber aqueous dispersion: Kevlar fibers were placed in a mixed alkaline solvent system composed of potassium hydroxide (KOH) and dimethyl sulfoxide (DMSO) and magnetically stirred at room temperature for 5–7 days to allow the Kevlar fibers to gradually dissociate, forming a deep red ANF / DMSO nanofiber dispersion. Subsequently, deionized water was added to the ANF / DMSO nanofiber dispersion for solvent replacement, causing the ANF nanofibers to precipitate and disperse in the aqueous phase. The solids were separated by vacuum filtration, and the filter cake was repeatedly washed with deionized water 3–5 times to remove residual KOH and DMSO. The resulting ANF nanofiber filter cake was redispersed in deionized water and homogenized by high-speed shearing to obtain a stable and homogeneous ANF nanofiber aqueous dispersion. The mass concentration of potassium hydroxide in the mixed alkaline solvent system is 1-5%; the mass-volume ratio of aramid fiber to the mixed alkaline solvent is 1g:100-500mL; The high-speed shear homogenization speed is 8000~15000 rpm, and the time is 5~20 minutes; The concentration of ANF / DMSO nanofiber dispersion is 10~20 mg / mL; the concentration of ANF nanofiber aqueous dispersion is 2~10 mg / mL. Step 2, Preparation of GN / DMSO dispersion and GN aqueous dispersion: Graphene (GN) powder was mixed with the surfactant polyvinylpyrrolidone (PVP), added to a solvent, and subjected to ultrasonic treatment using an ultrasonic cell disruptor under ice-water bath conditions to uniformly disperse the graphene and obtain a stable and uniform GN dispersion. The solvent is deionized water or DMSO; when the solvent is deionized water, a GN aqueous dispersion is obtained; when the solvent is DMSO, a GN / DMSO dispersion is obtained. The mass ratio of GN to PVP was 1:0.5~2, the ultrasonic power was 300~700 W, and the ultrasonic time was 1~3 h; the concentration of the GN dispersion was 0.5~5 mg / mL. Step 3, Preparation of CNT aqueous dispersion: Carbon nanotubes (CNTs) were mixed with the surfactant sodium dodecylbenzenesulfonate (SDBS), added to deionized water, and subjected to ultrasonic treatment using an ultrasonic cell disruptor under ice-water bath conditions to uniformly disperse the graphene and obtain a stable and uniform CNT aqueous dispersion. The mass ratio of CNT to SDBS is 1:1~3, the ultrasonic power is 300~700 W, and the ultrasonic time is 1~3 h; the concentration of the CNT aqueous dispersion is 0.5~5 mg / mL. Step 4, prepare the ANF / GN mixture: The ANF / DMSO nanofiber dispersion prepared in step 1 and the GN / DMSO dispersion obtained in step 2 are ultrasonically mixed to prepare an ANF / GN mixture. The mass ratio of ANF to GN in ANF nanofiber aqueous dispersion and GN / DMSO dispersion is 1~4:6~9; Step 5, prepare the ANF / GN / CNT mixture: An ANF\GN\CNT mixture was prepared by ultrasonic mixing of ANF nanofiber aqueous dispersion, GN aqueous dispersion and CNT aqueous dispersion. The mass ratio of ANF, GN and CNT in ANF nanofiber aqueous dispersion, GN aqueous dispersion and CNT aqueous dispersion is 1:4~8:2~6; Step 6, Integrated asymmetric structure forming: Under vacuum-assisted conditions, the ANF / GN / CNT mixture obtained in step 5 was filtered to form a dense ANF / GN / CNT film on the filter membrane surface as a reflective layer. After filtration, the mixture was transferred to a polytetrafluoroethylene mold, and the ANF / GN mixture obtained in step 4 was slowly poured into the mold to cover the ANF / GN / CNT film. Subsequently, the mold with the above-mentioned double-layer structure was pre-frozen on a copper plate at -20°C or -196°C for 4~24 hours, so that the ANF / GN / CNT reflective layer and the ANF / GN absorber layer would bond together through hydrogen bonding on the surface of ANF nanofibers during the freezing process, forming an asymmetric double-layer ice gel film. The thickness of the ANF / GN / CNT reflective layer is 10~200 μm; the thickness of the ANF / GN absorber layer is 0.1~5 mm; the absorber layer aerogel has an anisotropic or isotropic porous structure; Step 7: Immerse the bilayer ice gel film obtained in Step 6 in an ethanol solution containing 5-20 vol% acetic acid and perform solvent replacement treatment at -10 to -20°C for 36-48 hours. Acetic acid is used to catalyze the amidation crosslinking reaction between ANF nanofibers, further enhancing the interlayer bonding force and skeleton strength. After solvent replacement, remove the sample and place it in a freeze dryer, freeze-drying it at -50 to -60°C and 0-10 Pa for 48-72 hours to remove ice crystals through sublimation, obtaining an integrated asymmetric ANF-based electromagnetic shielding composite material.

[0022] Example 1 The preparation method of the asymmetric ANF-based electromagnetic shielding composite material of the present invention is as follows: Step 1, Preparation of ANF dispersion: 1g of Kevlar fiber and 3g of KOH were added to 100mL of DMSO and magnetically stirred for 7 days at room temperature to obtain a deep red ANF / DMSO dispersion with a concentration of 10mg / mL. 500mL of deionized water was added for solvent replacement, precipitating ANF nanofibers. After vacuum filtration, the filter cake was washed repeatedly with deionized water 5 times to remove residual KOH and DMSO. The filter cake was redispersed in deionized water and processed using a high-speed shear homogenizer at 8000 rpm for 30min to obtain an ANF nanofiber aqueous dispersion with a concentration of 2mg / mL.

[0023] Step 2, Preparation of GN dispersion: Mix 1 g GN powder with 1 g PVP, add to 500 mL DMSO, and sonicate for 2 hours using an ultrasonic cell disruptor (500 W power) under ice-water bath conditions to obtain a uniform GN / DMSO dispersion with a concentration of 2 mg / mL; Mix 1 g GN powder with 1 g PVP, add to 500 mL deionized water, and sonicate for 2 hours using an ultrasonic cell disruptor (500 W power) under ice-water bath conditions to obtain a GN aqueous dispersion with a concentration of 2 mg / mL.

[0024] Step 3, Preparation of CNT aqueous dispersion: Mix 1 g CNT with 2 g SDBS, add to 500 mL of deionized water, and sonicate for 2 hours using an ultrasonic cell disruptor (power 500 W) under ice-water bath conditions to obtain a uniform CNT aqueous dispersion with a concentration of 2 mg / mL.

[0025] Step 4, prepare ANF / GN mixture: Mix ANF / DMSO dispersion (10 mg / mL, 2 mL) with GN / DMSO dispersion (2 mg / mL, 40 mL) to make the ANF:GN mass ratio 2:8, and sonicate for 30 minutes to obtain a homogeneous ANF / GN mixture.

[0026] Step 5, prepare ANF / GN / CNT mixture: Mix ANF nanofiber aqueous dispersion (2 mg / mL, 10 mL), GN aqueous dispersion (2 mg / mL, 50 mL) and CNT aqueous dispersion (2 mg / mL, 20 mL) to make the mass ratio of ANF:GN:CNT 1:5:2. Sonicate for 30 min to obtain a uniform ANF / GN / CNT mixture.

[0027] Step 6, Integrated Asymmetric Structure Molding: Pour the obtained ANF / GN / CNT mixture into a Buchner funnel and filter under a vacuum of -0.08 MPa to form a dense film (50 μm thick). Transfer the film along with the filter membrane into a polytetrafluoroethylene mold, and slowly pour the obtained ANF / GN mixture into the mold to cover the film. Pre-freeze the mold at -20°C for 12 hours to allow the two layers to bond together via ANF hydrogen bonds.

[0028] Step 7: Immerse the obtained ice gel in an ethanol solution containing 10 vol% acetic acid and solvent-displace it at -10℃ for 48 h. Remove the sample and place it in a freeze dryer, freeze-drying it at -55℃ and 8 Pa for 48 h to obtain an integrated asymmetric ANF-based electromagnetic shielding composite material.

[0029] Performance testing: The electromagnetic shielding effectiveness of this material in the X-band (8.2-12.4 GHz) was tested using the waveguide method. The test results show that the average electromagnetic shielding effectiveness (SE) of this material can reach over 81 dB, with absorption loss (SEA) accounting for over 86% of the total shielding effectiveness, indicating that the material is mainly absorption-based and effectively reduces secondary electromagnetic pollution. Figure 1 This is a photograph of the ANF-based electromagnetic shielding composite material prepared in Example 1. It can be clearly seen from the figure that the film-aerogel has an asymmetric structure.

[0030] Figure 2a Here is a cross-sectional SEM image of the ANF-based electromagnetic shielding composite material prepared in Example 1; Figure 2b This is a SEM image of the ANF / GN aerogel absorbing layer in the ANF-based electromagnetic shielding composite material prepared in Example 1; Figure 2c This is a SEM image of the ANF crosslinking interface layer in the ANF-based electromagnetic shielding composite material prepared in Example 1; Figure 2d This is a SEM image of the ANF / GN / CNT dense reflective layer in the ANF-based electromagnetic shielding composite material prepared in Example 1. The image shows that the aerogel layer has a loose and porous structure, while the film layer has a dense structure, and there are no obvious gaps or cracks between the two layers.

[0031] Figure 3 This is a surface SEM image of the absorbing layer in the ANF-based electromagnetic shielding composite material prepared in Example 1; Figure 4 This is a surface SEM image of the reflective layer in the ANF-based electromagnetic shielding composite material prepared in Example 1. The image shows a clear asymmetric structure between the top and bottom layers. Figure 5 The graph shows the total electromagnetic shielding effectiveness of the ANF-based electromagnetic shielding composite material prepared in Example 1. As can be seen from the graph, the average total electromagnetic shielding effectiveness of Example 1 is about 81 dB.

[0032] Example 2 The difference between this embodiment and Embodiment 1 is that: In step 4, the mass ratio of ANF to GN is 4:6; In step 5, the mass ratio of ANF, GN, and CNT is 1:4:2; In step 6, a directional freezing method is used, in which the bottom of the mold is placed in liquid nitrogen to achieve directional freezing from bottom to top, and the pre-freezing time is 6 hours. In step 7, the volume fraction of acetic acid is 20 vol%.

[0033] The other steps are the same as in Example 1. Test results show that the material prepared in this example has an average electromagnetic shielding effectiveness of over 50 dB in the X-band.

[0034] Figure 6The graph shows the total electromagnetic shielding effectiveness of the ANF-based electromagnetic shielding composite material prepared in Example 2. As can be seen from the graph, the average total electromagnetic shielding effectiveness of Example 2 is more than 50 dB.

[0035] Example 3 The difference between this embodiment and Embodiment 1 is that: In step 4, the mass ratio of ANF to GN is 1:9; In step 5, the mass ratio of ANF, GN, and CNT is 1:8:6; In step 6, the thickness of the reflective layer is controlled at 100 μm, and the thickness of the absorption layer is 3 mm; In step 7, the acetic acid volume fraction is 5 vol%, and the freeze-drying time is 72 h.

[0036] The other steps are the same as in Example 1. Test results show that the material has higher conductivity, and the average electromagnetic shielding effectiveness in the X-band can reach 61 dB. The reflection loss (SER) is slightly increased, but absorption loss is still the main factor.

[0037] Figure 7 The graph shows the total electromagnetic shielding effectiveness of the ANF-based electromagnetic shielding composite material prepared in Example 3. As can be seen from the graph, the average total electromagnetic shielding effectiveness of Example 3 is about 61 dB.

[0038] Comparative Example 1 This comparative example provides a single-layer ANF / GN aerogel electromagnetic shielding material. The preparation method differs from that of Example 1 in that: no reflective layer is provided; it is prepared solely from an ANF / GN mixture by freeze-drying. Specifically: Step 1, Preparation of ANF dispersion: 1g of Kevlar fiber and 3g of KOH were added to 100mL of DMSO and magnetically stirred for 7 days at room temperature to obtain a deep red ANF / DMSO dispersion with a concentration of 10mg / mL. 500mL of deionized water was added for solvent replacement, precipitating ANF nanofibers. After vacuum filtration, the filter cake was washed repeatedly with deionized water 5 times to remove residual KOH and DMSO. The filter cake was redispersed in deionized water and processed using a high-speed shear homogenizer at 8000 rpm for 30min to obtain an ANF nanofiber aqueous dispersion with a concentration of 2mg / mL.

[0039] Step 2, Preparation of GN dispersion: Mix 1 g of GN powder with 1 g of PVP, add to 500 mL of DMSO, and sonicate for 2 h using an ultrasonic cell disruptor (500 W power) under ice-water bath conditions to obtain a uniform GN / DMSO dispersion with a concentration of 2 mg / mL. Step 3, Preparation of ANF / GN mixture: Mix ANF / DMSO dispersion (10 mg / mL, 2 mL) with GN / DMSO dispersion (2 mg / mL, 40 mL) to make the mass ratio of ANF:GN 2:8, and sonicate for 30 min to obtain a homogeneous ANF / GN mixture.

[0040] Step 4: Slowly pour the obtained ANF / GN mixture into the mold to cover the film. Place the mold in a -20°C freezer for 12 hours to allow the two layers to bond together via ANF hydrogen bonds.

[0041] Step 5: Immerse the obtained ice gel in an ethanol solution containing 10 vol% acetic acid and perform solvent replacement at -10℃ for 48 h. Remove the sample and place it in a freeze dryer, freeze-drying at -55℃ and 8 Pa for 48 h to obtain a single-layer ANF / GN aerogel electromagnetic shielding material.

[0042] Performance Testing: Electromagnetic shielding effectiveness was tested in the X-band. Due to the large internal pores and low conductivity of the aerogel, its average electromagnetic shielding effectiveness (SE) was only 50 dB, far lower than that of Example 1. This indicates that although the reflection coefficient is low, the lack of a reflective layer results in the absence of an internal absorption-reflection-reabsorption cycle mechanism. A single absorption layer cannot provide sufficient shielding effectiveness; a highly conductive reflective layer is necessary to achieve efficient shielding.

[0043] Comparative Example 2 This comparative example provides an asymmetric electromagnetic shielding material with an inverted structure. The preparation method is as follows: using an ANF / GN / CNT thin film as the absorbing layer and an ANF / GN aerogel as the reflective layer, an asymmetric electromagnetic shielding material is obtained.

[0044] Step 1, Preparation of ANF dispersion: 1g of aramid Kevlar fiber and 3g of KOH were added to 100mL of DMSO and magnetically stirred for 7 days at room temperature to obtain a deep red ANF / DMSO dispersion with a concentration of 10mg / mL. 500mL of deionized water was added for solvent replacement, precipitating ANF nanofibers. After vacuum filtration, the filter cake was washed repeatedly with deionized water 5 times to remove residual KOH and DMSO. The filter cake was redispersed in deionized water and processed using a high-speed shear homogenizer at 8000 rpm for 30min to obtain an ANF nanofiber aqueous dispersion with a concentration of 2mg / mL.

[0045] Step 2, Preparation of GN dispersion: Mix 1 g GN powder with 1 g PVP, add to 500 mL DMSO, and sonicate for 2 hours using an ultrasonic cell disruptor (500 W power) under ice-water bath conditions to obtain a uniform GN / DMSO dispersion with a concentration of 2 mg / mL; Mix 1 g GN powder with 1 g PVP, add to 500 mL deionized water, and sonicate for 2 hours using an ultrasonic cell disruptor (500 W power) under ice-water bath conditions to obtain a GN aqueous dispersion with a concentration of 2 mg / mL.

[0046] Step 3, Preparation of CNT aqueous dispersion: Mix 1 g CNT with 2 g SDBS, add to 500 mL of deionized water, and sonicate for 2 hours using an ultrasonic cell disruptor (power 500 W) under ice-water bath conditions to obtain a uniform CNT aqueous dispersion with a concentration of 2 mg / mL.

[0047] Step 4, prepare ANF / GN mixture: Mix ANF / DMSO dispersion (10 mg / mL, 2 mL) with GN / DMSO dispersion (2 mg / mL, 40 mL) to make the ANF:GN mass ratio 2:8, and sonicate for 30 minutes to obtain a homogeneous ANF / GN mixture.

[0048] Step 5, prepare ANF / GN / CNT mixture: Mix ANF nanofiber aqueous dispersion (2 mg / mL, 10 mL), GN aqueous dispersion (2 mg / mL, 50 mL) and CNT aqueous dispersion (2 mg / mL, 20 mL) to make the mass ratio of ANF:GN:CNT 1:5:2. Sonicate for 30 min to obtain a uniform ANF / GN / CNT mixture.

[0049] Step 6, Integrated Asymmetric Structure Molding: Pour the obtained ANF / GN / CNT mixture into a Buchner funnel and filter under a vacuum of -0.08 MPa to form a dense film (50 μm thick). Slowly pour the obtained ANF / GN mixture into a mold, and then cover the mixture with the film. Pre-freeze the mold in a -20°C freezer for 12 hours to allow the two layers to bond together via ANF hydrogen bonds.

[0050] Step 7: Immerse the obtained ice gel in an ethanol solution containing 10 vol% acetic acid and perform solvent displacement at -10℃ for 48 h. Remove the sample and place it in a freeze dryer, freeze-drying at -55℃ and 8 Pa for 48 h to obtain an asymmetric electromagnetic shielding material with an inverted structure.

[0051] Example 4 Figure 8This is a diagram showing the overall electromagnetic shielding effectiveness of the composite material prepared in Comparative Example 1; Figure 9 This is a diagram showing the overall electromagnetic shielding effectiveness of the composite material prepared in Comparative Example 2; Figure 10 This is a comparison chart of the absorption shielding effectiveness, reflection shielding effectiveness, and total shielding effectiveness of the composite materials in the examples and comparative examples. The chart shows that Example 1 has the highest electromagnetic shielding effectiveness, while Comparative Example 2 has a similar effectiveness. However, Example 1 exhibits higher absorption shielding effectiveness, which is attributed to its asymmetric absorption-reflection layer structure. This indicates that because the highly conductive ANF / GN / CNT layer directly faces the incident electromagnetic wave, its impedance matching is extremely poor, causing most electromagnetic waves to be reflected at the material surface, resulting in severe secondary electromagnetic pollution. In contrast, Example 1, with its porous aerogel absorption layer located on the incident surface, provides excellent impedance matching, allowing electromagnetic waves to preferentially enter the interior for absorption and loss, effectively solving the secondary pollution problem.

[0052] Example 5 The method of the present invention achieves the integrated construction of a dense reflective layer and a porous absorbent layer through solvent replacement and ice gel cryo-molding technology, and the layers are firmly bonded together inseparably through an ANF hydrogen bond network and physical cross-linking reaction.

[0053] Example 6 The ANF-based electromagnetic shielding composite material of the present invention can be applied in aerospace, military equipment, flexible electronics and other fields.

Claims

1. An asymmetric ANF-based electromagnetic shielding composite material, characterized in that, It includes a reflective layer and an absorber layer; the reflective layer is a ternary dense film composed of ANF, GN and CNT with a thickness of 10~200μm; the absorber layer is a porous aerogel layer composed of ANF and GN with a thickness of 0.1~5 mm. The reflective layer and the absorber layer are integrated through the hydrogen bond network and cross-linking bonds of ANF nanofibers.

2. A method for preparing asymmetric ANF-based electromagnetic shielding composite materials, characterized in that, Specifically: Step 1, Preparation of ANF / DMSO nanofiber dispersion and ANF nanofiber aqueous dispersion; Step 2, preparation of GN / DMSO dispersion and GN aqueous dispersion; Step 3, Preparation of CNT aqueous dispersion; Step 4: Prepare an ANF / GN mixture by ultrasonically mixing the ANF / DMSO nanofiber dispersion and the GN / DMSO dispersion; Step 5: Prepare an ANF\GN\CNT mixture by ultrasonically mixing the ANF nanofiber aqueous dispersion, GN aqueous dispersion and CNT aqueous dispersion; Step 6: Prepare a bilayer ice gel film using a mixture of ANF\GN\CNT and a mixture of ANF / GN; Step 7: Immerse the double-layer ice gel film in an ethanol solution containing acetic acid for solvent replacement treatment, and freeze-dry to obtain an asymmetric ANF-based electromagnetic shielding composite material.

3. The method for preparing the asymmetric ANF-based electromagnetic shielding composite material as described in claim 2, characterized in that, In step 1, specifically: Kevlar fibers were placed in a mixed alkaline solvent system consisting of potassium hydroxide and dimethyl sulfoxide and stirred for 5 to 7 days to form an ANF / DMSO nanofiber dispersion with a concentration of 10 to 20 mg / mL. Subsequently, deionized water was added to the ANF / DMSO nanofiber dispersion for solvent replacement. The solids were separated by vacuum filtration, and the filter cake was washed repeatedly with deionized water 3-5 times. The obtained ANF nanofiber filter cake was redispersed in deionized water and subjected to shear homogenization at 8000-15000 rpm for 5-20 min to obtain an ANF nanofiber aqueous dispersion with a concentration of 2-10 mg / mL.

4. The method for preparing the asymmetric ANF-based electromagnetic shielding composite material as described in claim 2, characterized in that, Step 2 specifically involves: Graphene powder was mixed with polyvinylpyrrolidone and added to deionized water or DMSO. The mixture was then subjected to ultrasonic treatment using an ultrasonic cell disruptor under ice-water bath conditions. The ultrasonic power was 300-700 W and the ultrasonic time was 1-3 h to obtain a GN aqueous dispersion or GN / DMSO dispersion with a concentration of 0.5-5 mg / mL.

5. The method for preparing the asymmetric ANF-based electromagnetic shielding composite material as described in claim 2, characterized in that, Step 3 specifically involves: Carbon nanotubes were mixed with sodium dodecylbenzenesulfonate and added to deionized water. The mixture was then subjected to ultrasonic treatment using an ultrasonic cell disruptor under ice-water bath conditions. The ultrasonic power was 300-700 W and the ultrasonic time was 1-3 h to obtain an aqueous dispersion of CNT with a concentration of 0.5-5 mg / mL.

6. The method for preparing the asymmetric ANF-based electromagnetic shielding composite material as described in claim 2, characterized in that, Step 6 specifically involves: Under vacuum-assisted conditions, the ANF / GN / CNT mixture is filtered to form a dense ANF / GN / CNT film on the filter membrane surface as a reflective layer. After filtration, the mixture is transferred to a polytetrafluoroethylene mold, and the ANF / GN mixture is slowly poured into the mold to cover the ANF / GN / CNT film. Subsequently, the mold with the above-mentioned double-layer structure is pre-frozen for 4-24 hours to form an asymmetric double-layer ice gel film.

7. The method for preparing the asymmetric ANF-based electromagnetic shielding composite material as described in claim 2, characterized in that, Step 7 specifically involves: A double-layer ice gel film was immersed in an ethanol solution containing acetic acid and subjected to solvent replacement treatment at -10 to -20°C for 36-48 hours. After solvent replacement, it was freeze-dried at -50 to -60°C and 0-10 Pa for 48-72 hours to obtain an asymmetric ANF-based electromagnetic shielding composite material.

8. The application of the asymmetric ANF-based electromagnetic shielding composite material as described in any one of claims 1-7 in flexible electronics.